Comparison of the single-lumen endotracheal tube and double-lumen endobronchial tube used in minimally invasive cardiac surgery for the fast track protocol - Kim, Hee Young; Baek, Seung-Hoon; Je, Hyung Gon; Kim, Tae Kyun; Kim, Hye Jin; Ahn, Ji Hye; Park, Soon Ji (Journal of Thoracic Disease; Vol 8, No 5 (May 01, 2016): Journal of Thoracic Disease, 2016)
Background: Minimally invasive cardiac surgery (MICS) has been more commonly performed due to the reduced amount of bleeding and transfusion and length of hospital stay. We investigated the feasibility of performing MICS using single-lumen endotracheal tube (SLT). Methods: We conducted a retrospective review of clinical data of 112 patients who underwent MICS between July 2012 and March 2015. The patients underwent MICS using a SLT or a double lumen endotracheal tube (DLT). The duration of intensive care unit (ICU) stay and mechanical ventilation were recorded and analyzed. Results: Of the 96 patients, 50 were intubated with a SLT and 46 were intubated with a DLT. Anesthetic induction to skin incision time, surgical time and total anesthetic time were significant decreased in the SLT group (P